دافعية إنجاز طالبات قسم اللغة العربية وعلاقتها بالتحصيل الدراسي على أساس نظرية سجونج (Dale H. Schunk) - Hamdy, Mohammad Zainal; Machmudah, Umi (Mayada: al-Multaqa al-Ilmy al-Alamy lil-Dirasat al-Arabiyah; Vol 1 No 1 (2023): مجموعة البحوث - الملتقى العلمي العالمي للدراسات العربية, 2024)
Indicators of motivation are extremely important to the learning and teaching process. Motivation is a basic condition for the learner to achieve major educational goals, whether in the acquisition of knowledge, which is a cognitive aspect for the learner, or in the formation of values and attitudes, which is an emotional aspect in the student’s personality, or in the formation of various skills, which is a sensory-motor aspect. In this research, the researcher wants to know the extent of the relationship between achievement motivation and academic achievement in the Arabic language at this university, especially among female students at Darul Ulum University Banyuanyar Pamekasan. The researcher uses a quantitative correlational type, which is research that aims to determine whether there is a relationship between two variables or several variables, and from the results of the conclusion that the relationship between these two aspects has a low impact, only 12.3% of all aspects that can affect the Academic achievement of female students. among female students at Darul Ulum University Banyuanyar Pamekasan. With a factor of 0.111 using the Pearson product-moment correlation formula. أن مؤشرات الدافعية أمر في غاية الأهمية لعملية التعلم و التعليم فالدافعية شرط أساسي عند المتعلم لتحقيق الغايات التربوية الكبرى سواء في تحصيل المعارف وهو جانب معرفي عند المتعلم أو في تكوين القيم و الاتجاهات وهو جانب وجداني في شخصية التلميذ أو في تكوين المهارات المختلفة وهو جانب حسي حركي. في هذا البحث يريد الباحث معرفة مدى العلاقة بين دافعية الإنجاز والتحصيل الدراسي للغة العربية في هذه الجامعة ، وخاصة في طالبات قسم اللغة العربية المرحلة الخامسة جامعة دار العلوم بانيوأنيار باميكاسان. ويستخدم الباحث الارتباطي  من نوع الكمي وهو البحث الذي يهدف إلى تحديد ما إذا كانت هناك علاقة بين متغيرين أو عدة متغيرات وأفراد البحث جميع الطالبات عدد 26 طالبات من غير عشوئية بالتحليل Pearson product - moment correlation   ومن نتائج استنتاج أن العلاقة بين هذين الجانبين لها تأثير منخفض، فقط 12.3% من جميع الجوانب التي يمكن أن تؤثر على التحصيل الدراسي لدي طالبات المرحلة الخامسة جامعة دار العلوم بانيوأنيار باميكاسان مدورا. بمعامل 0.111 باستخدام الصيغة Pearson product-moment correlation.